2003
DOI: 10.1037/0735-7028.34.3.318
|View full text |Cite
|
Sign up to set email alerts
|

What do psychologists think about mandatory continuing education? A survey of Pennsylvania practitioners.

Abstract: Would psychologists voluntarily participate in continuing education (CE) if it were not mandatory to do so? Does CE help make psychologists more effective clinicians? These and other aspects of mandatory CE were explored in a survey of 168 licensed psychologists in Pennsylvania. Although 75% of respondents were in favor of mandatory CE, the sample was divided over the question of whether they would obtain the required credits if not mandatory. Forty-five percent of respondents reported that attendance at CE pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 7 publications
10
58
1
Order By: Relevance
“…This mirrors the general positive attitude and important placed on continuing education in this field (Neimeyer et al, 2009;Sharkin & Plageman, 2003). Additionally, the vast majority of participants "somewhat" to "strongly" agreed that they are putting the necessary amount of time and money into their continuing education activities (see Table 1).…”
Section: Continuing Education Attitudessupporting
confidence: 55%
See 1 more Smart Citation
“…This mirrors the general positive attitude and important placed on continuing education in this field (Neimeyer et al, 2009;Sharkin & Plageman, 2003). Additionally, the vast majority of participants "somewhat" to "strongly" agreed that they are putting the necessary amount of time and money into their continuing education activities (see Table 1).…”
Section: Continuing Education Attitudessupporting
confidence: 55%
“…Willingness to participate in continuing education activities was shown in Sharkin and Plageman's (2003) study of Pennsylvania psychologists, in which 18% of the 168 participants indicated that they often attend continuing education activities when not required, and 47% reported sometimes attending when not required. The majority of the participants reported that what they had learned could be implemented into their practice, and over 85% believed that continuing education "sometimes" or "frequently" made them more effective in practice.…”
Section: Attitudes Toward Continuing Educationmentioning
confidence: 92%
“…The primary reasons given for choosing a particular CE program tend to involve cost, convenience, topic, and location (Sharkin & Plageman, 2003).…”
Section: Continuing Education Programsmentioning
confidence: 99%
“…In earlier work, noted, however, that even within nonmandating jurisdictions, the majority of psychologists favored CE mandates, with only 25% disagreeing with mandating CE. This figure (25%), as noted by , is conspicuously close to the 25% to 30% of psychologists who likely would not participate in CE in the absence of CE mandates (Phillips, 1987;Sharkin & Plageman, 2003;VandeCreek et al, 1990), raising significant questions regarding whether the opposition to mandated CE is heavily populated by what Phillips has termed CE "laggards. "…”
Section: Resultsmentioning
confidence: 85%